Transportation technologies, sharing economy, and teleactivities: Implications for built environment and travel. (March 2021) - Mouratidis, Kostas; Peters, Sebastian; van Wee, Bert
Highlights: A synthesis of around 200 studies on app-enabled developments, travel behavior, and the built environment is presented. Bikesharing, carsharing, and autonomous buses could reduce car travel. Private autonomous cars and ridesourcing/ridehailing may increase motorized travel. The implications of drones and robots for land use and travel are still unclear. COVID-19 is likely to reshape the importance of teleactivities, the sharing economy, and transportation technologies. Abstract: This paper reviews how teleactivities, the sharing economy, and emerging transportation technologies – components of what we could call the "App City" – may influence travel behavior and the built environment. Findings suggest that teleactivities may substitute some trips but generate others. Telework and teleconferencing may reduce total travel. Findings on the sharing economy suggest that accommodation sharing increases long-distance travel; bikesharing is conducive to more active travel and lower car use; carsharing may reduce private car use and ownership; ridesourcing (ridehailing) may increase vehicle miles traveled; while the implications of e-scooter sharing, ridesharing, and Mobility as a Service are context-dependent. Findings on emerging transportation technologies suggest that private autonomous vehicles and urban air mobility may increase total travel, whereas autonomous buses may lead to reduced car use. Implications of App Cities for the built environment include new transport systems and land use changes due to behavioral changes.